The Algerian people's party (P.P.A.) inkabylie: from the preponderance of the ""revolutionaries"" to the seizure of the ""maquisards"" (1939-1954) - sadaoui, mostafa (Journal of Social Sciences and Humanities, 2020)
Notwithstanding that the political form of the anti-colonial struggle had originated in Algeria in urban areas, the Kabylie rural region par excellence contributed considerably. It should be noted that from the twenties of the last century, the above-mentioned region never ceased to become a major bastion of the nationalist current claiming independence.This process was greatly accelerated during World War II, so that the socialeconomic changes that they engendered facilitated the spread and radicalization of this movement in Kabylia. This favored the emergence of a local command composed of elements in the prime of life, and whose homogeneity is reinforced by several common characteristics such as: the similar geographical origin (high Kabylia), the affiliation to social groups relatively favored, the passage through the high school Ben Aknoun (Algiers), etc .. From the beginning, this team aligned itself with the positions of the most radical wing in the party administration, led by Dr. Debaghine.This being so, the weakening of this wing following a series of crises shaking the party between 1949 and 1950, it provoked the eviction of the local management concerned.This led to the rise of a new management team, different in many ways from its predecessors, marked - in parallel - by many traits in common between its elements, such as membership of the group of "maquisards"already in revolt against colonialism for several years, added to the fact that they are almost all from low Kabylie, without forgetting their level of education very modest compared to their predecessors ... At first glance, this new direction let believe that it was in perfect symbiosis with the party administration, but the evolution of events quickly revealed the illusion of such a belief. This was confirmed by its alliance, from the first opportunity presented, with the activists who had formed a new organization, as well as its decisive contribution to the initiation of the insurrectional process of November 1, 1954